Comportamento de acasalamento e cuidado parental no pseudoescorpião neotropical Americhernes betaniae Mahnert, 1979 (Arachnida: Chernetidae) - Gonçalvez, Thalita Nunes; Tizo, Alinne Ferreira Silva; Pedroso, Everton Tizo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
Pseudoscorpions reproduce indirectly, transferring a spermatophore deposited on the substrate. In Cheliferoidea, males perform an elaborate ritual involving pedipalps vibrations and a mating ‘dance’ before depositing the spermatophore in the presence of the female. Thus, this study investigated the reproductive behavior and parental care of the neotropical pseudoscorpion Americhernes bethaniae, from populations collected in the Brazilian Cerrado. Pseudoscorpions were collected from live tree trunks and stored in the laboratory for behavioral observations. In the case of A. bethaniae, courtship involved ritual vibration of the pedipalps, followed by eight distinct reproduction stages: approach, sex identification, fixation, dance, spermatophore formation, spermatophore transfer, and then either a fight or resumption of the process. Females built silk nests and produced an embryonic sac about 15 days after mating. Three days after the first ecdysis of the juveniles, the mother left the silk chamber. The male remained with the female until she sealed herself inside the silk nest, but did not contribute to the offspring care. This guarding behavior may suggest a strategy to ensure paternity.